Study of Indicators of Nervous-Psychological Resistance and Social Maturity in Military Servants During the Message of Psycho - Mozgovyi, Viktor I. (Psychological Counseling and Psychotherapy, 2021)
The article is devoted to theoretical and empirical research, important personal characteristics of servicemen: neuropsychological stability and socio-psychological maturity, which are the focus of psychological influence by the psychologist of the military unit at all major stages of military activity from conscription to discharge. The article empirically examines the system of relationships between indicators of neuropsychological stability, socio-psychological maturity and social relations in military servicemen at the stages of adaptation and performance of tasks. A correlation analysis was performed, according to Pearson, with indicators of neuropsychological stability, social maturity and the quality of relationships with the immediate social environment. As a result of the analysis of the obtained data, it was found that social maturity is directly related to the quality of social relations in a serviceman, both in the family and in the military, and tends to increase during military service. The level of stability of neuropsychological stability associated with the growth of social maturity due to the reflex component. The servicemen performing the assigned tasks have a positive dynamics of increasing the level of social maturity due to the reflexive and moral component, which indicates their personal and professional growth due to organized psychological support. The tasks and the expected result of psychological support at the stages of adaptation and performance of tasks as assigned are determined. The main vectors of psychological influence on the part of a military psychologist are indicated. to increase the level of neuropsychological stability and socio-psychological maturity in the military.